Institutional Conditions For Stakeholder CSR - A Qualitative Comparative Analysis - Backhaus, Marius (2008)
This dissertation undertakes a comparative investigation of national institutional patterns underlying environmental CSR, employee CSR, investor CSR, and social CSR. For this purpose, I draw on different case studies and comparative analyses to indicate the occurrence of the types of stakeholder CSR in the 21 considered countries. Amable's (2003) varieties of capitalism approach is used to classify the prevalence of five institutional characteristics for the countries of the sample. By means of qualitative comparative analysis (QCA) (Ragin 1987; 2000), the causal links between certain institutional characteristics or combinations of characteristics (configurations) and the four types of stakeholder CSR are analysed. The QCA method is particularly well fit for fields displaying causal complexity and has been advocated for use in CSR research (Gond et al 2008; Gjolberg 2007). I point out several institutional complementarities between institutions and stakeholder CSR as well as the predominance of institutional configurations associated with coordinated market economies for environmental and employee CSR and the predominance of institutional configurations associated with liberal market economies for investor and social CSR. However, the most profoundly supported findings of the analysis are the complexity of institutional conditions and the prevalence of multiple causal paths leading to the different types of stakeholder CSR.